Antibacterial Activity of Mangrove Root Extracts from Ngurah Rai Mangrove Forest, Denpasar-Bali - Made Dharmesti Wijaya; Anak Agung Gede Indraningrat (Biology, Medicine, & Natural Product Chemistry, 2021)
The increasing rate of antimicrobial resistance in the past decades has motivated the search for novel antibacterial compounds to overcome infectious diseases. Among diverse natural sources, mangrove ecosystems offer untapped sources of biological active compounds for future antibacterial medicine. This research was aimed to evaluate antibacterial activities of crude extracts of four dominant mangrove plants from the Ngurah Rai Mangrove Forest namely Rhizophora mucronata, Avicennia marina, Rhizophora apiculata, and Sonneratia alba. Roots of these four plants were extracted using methanol, chloroform, and n-hexane. These crude extracts were tested against two Gram positive bacteria (Staphylococcus aureus and Streptococcus mutans) and two Gram negative bacteria (Escherichia coli dan Klebsiella pneumoniae) by disc difussion assay. We found that 3 mg/mL of N-hexane crude extracts from R. apiculata yielded the highest zone of inhibition of 8.64 mm against S. aureus. While, 3 mg/mL of chloroform crude extract of R. apiculata yielded the highest inhibition of 19.83 mm against S. mutans. Unfortunately, no zone of inhibition was observed when crude extracts were tested against Gram negative indicator strains. Our results indicate that the root crude extracts of R. apiculata yielded the highest zone of inhibition against Gram positive indicator strains compared to root crude extracts of R. mucronata, S. alba, and A. marina. Further research is required to determine the antibacterial activities of the mangrove crude extracts against other bacterial indicator strains to determine their spectrum of activities.